Leading with questions how leaders discover powerful answers by knowing how and what to ask - Marquardt, Michael J.; Tiede, Bob (Ascent Audio, 2023)
A unique and powerful strategy for leading others In this newly revised third edition of Leading with Questions, renowned global leadership consultants Michael Marquardt and Bob Tiede describe how to ask powerful questions that generate short-term and long-term results and success. They show you how effective leaders use questions to encourage participation and teamwork, foster creative thinking, empower others, create relationships with customers, and solve problems. The authors offer step-by-step guidance on the process of learning the art of questioning and techniques-like active listening and follow-ups-you can use in myriad situations with individuals, teams, and entire organizations. You'll also find: - The most recent research on how questions change people and companies for the better - Interviews with over forty world-leading executives and managers from a wide variety of industries and regions - Concrete, hands-on strategies for generating short-term results and long-term change with questions Perfect for managers, executives, and other business leaders, Leading with Questions will earn a place on the bookshelves of anyone interested in better engaging with and leading others.
Online resource; title from title details screen (O'Reilly, viewed June 13, 2023)
Keywords: Leadership; Communication in management; Questioning; Communication en gestion; Interrogation; Audiobooks; Livres audio